The New Moral Absolutism in Catholic Moral Teaching: A Critique Based on Veritatis Splendor - Mike, Károly (Religions, 2025)
This paper examines a recent shift in Catholic moral teaching, characterized by the emergence of a ‘new moral absolutism’, in which certain acts traditionally subject to prudential judgment—such as the death penalty, ecological harm, and restrictive migration policies—are increasingly portrayed as universally and gravely wrong in our age. Simultaneously, traditional moral absolutes, especially in sexual and life ethics, have experienced cautious relativization. Drawing on the framework of Veritatis Splendor (1993), the paper critiques the approach of this new moral absolutism, arguing that it undermines the proper role of individual conscience and situational discernment while failing to provide coherent guidance on complex moral dilemmas. It links its emergence to proportionalist ethics: when traditional moral absolutes are relativized, new types of wrongs take their place. The paper proposes a return to the principles of Veritatis Splendor, advocating for a nuanced approach that preserves the constant and limited set of absolute negative norms and encourages the formation and use of conscience for all other matters.